ADAPTING TO CRISIS: AN ANALYSIS OF ORGANIZATIONAL INITIATIVES IN RESPONSE TO THE COVID-19 PANDEMIC (Lex localis - Journal of Local Self-Government, 2024)
The COVID-19 pandemic has brought organizational challenges from disruption. Organizations have made several efforts to ensure their survival and sustainability during this period. The current paper, therefore, tries to understand the initiatives adopted by the Information Technology (IT) sector in India towards managing such disruptions. It discusses responses regarding workplace flexibility and digital infrastructure, human resource (HR) practices, and employee well-being measures. This study falls under descriptive research design and uses 397 responses from structured questionnaires administered to employees working within the Delhi NCR region. The findings indicate that WFH implementation by IT organizations is successful with flexible timing, e-HRM systems, and training programs for sustaining support to keep employees engaged at work. Meanwhile, gaps were discovered in the areas of financial support schemes and occupational health programs for on-site workers who rated these areas relatively lower. These results highlight that while IT firms demonstrated resilience and adaptability through digital innovation and flexible work practices, greater attention is required to address employee security and holistic protection. The study contributes to the academic discourse on crisis leadership, HRM practices, and organizational behavior by providing insights into how IT organizations navigated the pandemic. It also offers practical implications for managers and policymakers to institutionalize flexible, technology-driven, and employee-centered practices as part of long-term strategies. Results underscore technological readiness that has to be matched with holistic human-centered policies to develop a post-pandemic organization as resilient.